'Isolated actions against non-Aryans are to be strictly discontinued' the Hitler Youth and violence against Jews. Issue 3 (3rd July 2021) - Postert, André
ABSTRACT: Historiography has long since cleared up a myth from the post-war period: in Nazi Germany, violence against Jews did not come solely from the Sturmabteilung and Schutzstaffel. Even children and teenagers were involved and became perpetrators. This article focuses on the difficult relationship between the Hitler Youth as the state youth organization and the antisemitic street violence. Official guidelines existed which prohibited young people from arbitrarily using force. In what context did these prohibitions arise? And what effect did they have? During Kristallnacht 1938, schoolchildren and adults were involved in riots in considerable numbers. How should the bans on violence be interpreted and what do they say about a society in which violence was, and became, everyday life?